Ejercicio y actividad física como herramienta terapeuta y alternativa para la población con trastornos depresivos - Sandra Carolina Hernandez Bueno (2024)
Year after year, cases of depressive disorders are increasing worldwide, whether due to social, environmental, physical, even political and economic factors, this has generated that the needs in mental health are considerable throughout the globe, that is why this study aims to show that physical activity and exercise can be a therapeutic alternative in this field of human health, for this purpose, members of the community of the National Pedagogical University of Colombia who are part of the GOAE guidance and follow-up groups have been taken as a sample. Considering the sociodemographic data and the Beck Depression Inventory applied at the beginning and at the end of the study, a characterization of the population is made, where people who attend psychological and psychiatric therapy participate, and in some cases, there is existing pharmacology. The results obtained regarding the internal reliability index of Cronbach's Alpha for the initial test are 0.743 and for the final test 0.734 indicating a high reliability. The results of the comparison of the BDI - II tests show that exercise and physical activity reduce depression scores, having positive effects uniformly in populations attending psychological and psychiatric therapy without medication as well as in those with a pharmacological prescription present.